Shifting patterns of disparities in unintentional injury mortality rates in the United States, 1999-2016 - Cheryl J. Cherpitel; Yu Ye; William C. Kerr (Pan American Health Organization, 2021)
Objectives. To analyze changes in racial/ethnic disparities for unintentional injury mortality from 1999-2016. Methods. Mortality data are from the National Center for Health Statistics (NCHS) for all unintentional injuries, analyzed separately by injury cause (motor vehicle accidents [MVA], poisonings, other unintentional) for white, black, and Hispanic populations within four age groups: 15-19, 20-34, 35-54, 55-74 for males and for females. Results. Rates across race/ethnic groups varied by gender, age and cause of injury. Unintentional injury mortality showed a recent increase for both males and females, which was more marked among males and for poisoning in all race/ethnic groups of both genders. Whites showed highest rates of poisoning mortality and the steepest increase for both genders, except for black males aged 55-74. MVA mortality also showed an increase for all race/ethnic groups, with a sharper rise among blacks, while Hispanics had lower rates than either whites or blacks. Rates for other unintentional injury mortality were similar across groups except for white women over 55, for whom rates were elevated. Conclusions. Data suggest while mortality from unintentional injury related to MVA and poisoning is on the rise for both genders and in most age groups, blacks compared to whites and Hispanics may be suffering a disproportionate burden of mortality related to MVAs and to poisonings among those over 55, which may be related to substance use.